437. SURGEON'S BEHAVIOR STEERING PATIENTS TO PARTICIPATE IN A CLUSTER RANDOMIZED TRIAL ON ACTIVE SURVEILLANCE FOR ESOPHAGEAL CANCER. (24th September 2022) - Van Der Zijden, Charlène J; de Veer, M; Hermus, M; van der Wilk, BJ; Wijnhoven, BPL; Stiggelbout, AM; Dekker, JWT; Coene, PPLO; van Busschbach, JJ; van Lanschot, JJB; Lagarde, SM; Kranenburg, LW
Abstract: Shared decision making (SDM) is used to involve patients in the decision-making process. Researchers have shown that clinicians, often unintendedly, use steering behavior which may persuade patients to choose for a specific treatment. Well-balanced information provision towards patients can be challenging when participation in a randomized trial is discussed. This study investigates if and how surgeons use steering behavior when patients are eligible to participate in a stepped-wedge cluster randomized trial. Patients with locally advanced esophageal cancer, planned to undergo neoadjuvant chemoradiotherapy (nCRT) followed by standard surgery, were included prior to their first surgical consultation. During this consultation, the surgeon discussed the possibility to participate in a trial on active surveillance after nCRT as experimental treatment. Standard care (i.e. surgical resection) was offered to patients who refused participation. Randomization occurred on the institutional level and therefore both surgeons and patients were aware of allocated treatment in the experimental arm before making a decision. Consultations were audiotaped and transcribed verbatim. Data were analyzed using thematic content analysis. Twenty consultations were recorded between June and December 2020. Surgeons used various techniques to steer patients towards a specific treatment, mostly towards participation. An imbalanced presentation of pros and cons of treatment options probably influenced patients' preferences: positive framing of active surveillance was used to steer patients towards opting for active surveillance, negative framing of active surveillance was used to make surgical resection more attractive. Besides using steering language, also the timing at which the alternative treatment option was discussed resulted in more focus on either of the treatment options. Various types of steering behavior were identified, including an imbalanced presentation of pros and cons, steering language and the timing at which different treatment options were discussed. Awareness of steering behavior in clinicians is the first step in improving objective information provision and thus shared decision making.